Creative self-efficacy: a comparative study of outstanding and ordinary students in the United Arab Emirates - Ellala, Ziyad Kamel; Abu-Attiyeh, Jamal Hassan; Kaba, Abdoulaye; Jabarah , Tamim Ahmed (Creativity Studies, 2023)
This study investigated the self-efficacy performance of outstanding and ordinary students. The study determined the level of creative self-efficacy among outstanding and ordinary students. A total of 76 undergraduates participated in the study, 37 outstanding students, and 39 ordinary students. Data were collected using an online survey questionnaire. The questionnaire consisted of the Abbott scale of creative self-efficacy. The scale contains 21 items that cover self-efficacy in creative thinking and self-efficacy in creative performance. The findings of the study showed that the level of creative self-efficacy is high among the participants. The results of the study revealed statistically significant differences due to gender variables in favour of male students. Similarly, significant differences are found in the total score of the Abbott scale of creative self-efficacy in favour of the outstanding students. The study offers several recommendations.